Maintenance of the appropriate depth of anesthesia without hypotention during enflurane anesthesia - KOBAYASHI, Yoshiro; YASUDA, Seiichi; SHIGEMATSU, Toshiyuki; MIYAZAWA, Noriko; HIYAMA, Atsuko (Nihon Rinshō Masui Gakkai shi, 1991)
For the purpose of obtainning appropriate depth of anesthesia and preventing severe hypotension during the anesthesia with enflurane, we examined the four methods; I: adjustment of concentration of inspired enflurane, II: Postural change of the patients, III: an increase in volume of infusion, IV: continuous administration at low concentration of dopamine. Through the method IV, the decrease in blood pressure was the least and the duration of the time of hypotension was the shortest. Those indicate that continuous administration of low concentration of dopamine is useful during enflurane anesthesia.